Vozes do sucesso: uma análise dos discursos sobre os vícios e virtudes da voz na mídia brasileira contemporânea - Soares, Thiago Barbosa (2018)
This paper analyzes discourses about what can be called the voices of success produced and / or conveyed by the great contemporary Brazilian media. More precisely, we describe and interpret the process of meaning production in statements made and formulated by Brazilian media discourses that manifestly deal with the voice of subjects whose success stems from their vocal performance, especially in the context of music. Thus, when we consider the postulate of the Discourse Analysis formulated by Pêcheux (2009) that subject and meaning are at the same time constituted in the historical movement, we understand that the words about the voice of success produce, at the same time, the senses and the subjects inside. Before this picture, we investigate what is said and how the voice is stated in the discourse of success in the current Brazilian society and the differences in the treatment of the voice of those who figure in the media world. Specifically, we aim to understand what distinctions may exist in terms of the production of meanings of the voices of success when disseminated by specialized or traditional, conservative or progressive vehicles of medium and large circulation. To do so, we analyzed a corpus consisting of texts from Rolling Stone, Billboard, Carta Capital e Veja and the Folha de São Paulo and O Estado de S. Paulo newspapers, published between January 2010 and December 2015. From this, we verified which is said of the voice, especially in the mainstream media, in order to reproduce inequalities and support various effects of sense of success in texts with massive circulation. In view of this, we find that there is a silencing of stigmatized voices within the media universe and, as one of its repercussions, there is a symbolic constellation in the collective imaginary, on which the reproduction of the statements of the voices of media success weighs. We observe the existence of a vocal aesthetic whose origin is at the junction of the cultural entertainment industry with the mainstream media, aiming at the dissemination of the voices of success. The methodological procedures adopted in the development of this study are based on qualitative research, in the realization of which we seek to identify regularities / irregularities, continuities and discontinuities of linguistic-discursive units of utterances within relatively distinct ideological orientations concerning speeches about subjects' voices of media success.